On the potential of Raman‐spectroscopy‐based carbonate mass spectrometry. (6th December 2012) - McKay, Nicholas P.; Dettman, David L.; Downs, Robert T.; Overpeck, Jonathan T.
<x xml:space="preserve">Abstract</x> The potential for using Raman spectroscopy to measure stable oxygen isotope ratios (18O/16O) in carbonates is evaluated by measuring the Raman spectra and isotope ratios of a suite of 60 synthesized, 18O‐enriched calcite crystals ranging in composition from natural abundance (0.2 mole‐% 18O) to 1.2 mole‐% 18O. We determined the Raman‐inferred isotopic ratios (RRaman) by fitting curves to the ν1 symmetric stretching peak at 1086 cm−1 and the smaller satellite peak, associated with the ν1 stretching mode of singly substituted carbonate groups (C16O218O) at 1065 cm−1. The ratio of the two peak areas shows a 1:1 correspondence with the 18O/16O ratios derived from standard mass spectrometry methods, confirming that the relative intensities of the ν1 symmetric stretching peaks is a direct measure of the isotopic ratio in the carbonates. The 1‐sigma uncertainties of the RRaman values of the individual crystals were 0.00079 (384‰ PDB) and 0.00043 (210‰ PDB) for the four‐crystal sample means. This level of uncertainty is much too high to provide significant estimates of natural variability; however, there are multiple prospects for improving the accuracy and precision of the technique. Carbon isotope ratios in carbonates cannot be measured by our approach, but our results highlight the potential of Raman‐based isotope ratio measurement for C and other elements in minerals and organic compounds. Copyright © 2012 John Wiley & Sons, Ltd.